Pengaruh Bimbingan Kelompok dengan Media Audio Visual terhadap Motivasi Belajar Siswa di MTs Negeri 4 Jakarta - Rianka Anindya Rahmadhita; Sigit Muryono (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research investigated the impact of group guidance with audio-visual media on learning motivation at MTs Negeri 4 Jakarta. A quantitative approach with a One Group Pretest Posttest experimental design was employed. Purposive sampling was used to select eighth-grade students as participants. Validity testing of the research instrument involved 20 statements, with 15 deemed valid and 5 invalid. The instrument demonstrated reliable validity with a Cronbach's Alpha coefficient of 0.675, surpassing the 0.60 threshold. Data analysis using the Wilcoxon test showed that 6 students experienced improved learning motivation, with an average increase of 3.50. This highlights the significant influence of group guidance with audio-visual media on students' learning motivation. Hypothesis testing revealed a significant effect, with an Asymp.Sig (2-tailed) value of 0.027 below the 0.05 significance level. Thus, the null hypothesis was rejected, indicating an impact of group guidance with audio-visual media on students learning motivation at MTs Negeri 4 Jakarta.